Trunk Neuromuscular Function in People With Knee Disorders: A Systematic Review With Meta-Analysis and Gap Map. - da Silva, Júlia C P [UNESP]; da Silva, Théo M B; Chia, Lionel; Bazett-Jones, David M; Pappas, Evangelos; de Azevedo, Fábio M [UNESP]; Briani, Ronaldo V [UNESP]; Waiteman, Marina C [UNESP] (Human Kinetics, 2025)
CONTEXT: Altered trunk kinematics have been reported in people with knee disorders and may be driven by neuromuscular deficits in the trunk muscles. Yet, no study has synthesized the evidence for trunk neuromuscular function in people with knee disorders compared with those injury-free. OBJECTIVE: To compare trunk neuromuscular function between people with and without knee disorders. EVIDENCE ACQUISITION: We searched 5 databases from inception to September 2024 for observational studies comparing trunk muscle strength, endurance, stability, and electromyography- or ultrasound-derived measures in people with and without knee disorders. Meta-analyses were conducted for each knee disorder when possible. Outcome-level certainty was assessed using Grading of Recommendations Assessment, Development, and Evaluation, and an evidence gap map was created. EVIDENCE SYNTHESIS: Twenty-three studies met the inclusion criteria across 4 knee disorders (ie, patellofemoral pain, ACL deficiency and reconstruction and knee osteoarthritis. People with patellofemoral pain presented with lower lateral trunk flexion strength and endurance (standardized mean differences, -0.48 to -0.54; 95% CI, -0.80 to -0.25) and lower anterior flexion and extension endurance (standardized mean differences, -1.19 to -1.47; 95% CI, -2.69 to -0.26), but no differences for erector spinae onset timing and external oblique amplitude activation during stepping and squatting tasks, compared with controls. We identified very limited evidence for studies investigating ACL deficiency/reconstruction and knee osteoarthritis populations. CONCLUSION: The lower lateral trunk strength and endurance, as well as lower trunk anterior and extension endurance in people with patellofemoral pain are consistent with previously reported alterations in trunk/lower limb frontal plane kinematics in this population. Further studies investigating trunk neuromuscular function are warranted to identify specific targets that may optimize rehabilitation of people with knee injuries or osteoarthritis.